To your tents, O Israel! : the terminology, function, form, and symbolism of tents in the Hebrew Bible and the ancient Near East - Homan, Michael M. (Culture and history of the ancient Near East, 2002)
An examination of the function, form and symbolism of ancient tents, specifically in the Hebrew Bible, but also in the greater context of the Ancient Near East. It explores the terminology associated with tents, along with their manifold usage: domiciliary, military, nuptial and religious.